Penerapan Model Multidimensional Scaling dalam Pemetaan Brand Positioning Internet Service Provider - Robertus Tang Herman (The Winners, 2010)
In this high-tech era, there have been tremendous advances in tech-based products and services. Internet is one of them that have widened the world’s eyes to a new borderless marketplace. High competition among internet service providers has pushed companies to create competitive advantage and brilliant marketing strategies. They undertake positioning mapping to describe product or service’s positioning amongst many competitors. The right positioning strategy becomes a powerful weapon to win in the battle. This research is designed to create positioning mapping based on perceptual mapping. The researcher uses Multidimensional Scaling and image mapping to achieve this research goal. Sampling is using non-probability sampling in Jakarta. Based on non-attribute approach, the research findings show that there is similarity between two different brands. Thus, both brands are competing against one another. On the other hand, CBN and Netzap provider reflect some differences to others. And some brands require some improvements in terms of network reliability.